Fertility decline and the heights of children in Britain, 1886 - 1938 - Timothy J. Hatton; Richard M. Martin (Institute for the Study of Labor (IZA), 2009)
In this paper we argue that the fertility decline that began around 1880 had substantial positive effects on the health of children, as the quality-quantity trade-off would suggest. We use microdata from a unique survey from 1930s Britain to analyze the relationship between the standardized heights of children and the number of children in the family. Our results suggest that heights are influenced positively by family income per capita and negatively by the number of children or the degree of crowding in the household. The evidence suggests that family size affected the health of children through its influence on both nutrition and disease. Applying our results to long-term trends, we find that rising household income and falling family size contributed significantly to improving child health between 1886 and 1938. Between 1906 and 1938 these variables account for nearly half of the increase in heights, and much of this effect is due to falling family size. We conclude that the fertility decline is a neglected source of the rapid improvement in health in the first half of the twentieth century.
Keywords: I32; J13; N33; N34; 330; Fertility decline; heights of children; health in Britain; Fruchtbarkeit; Demographischer Übergang; Kinder; Gesundheit; Großbritannien